Sex-dependent variations in anti-nociceptive and antipyretic effects of rhizome and stem extract of Schumannianthus dichotomus Roxb. in male and female mice - Mohammad Anwarul Basher (Universitas Gadjah Mada, 2020)
Schumannianthus dichotomus (Roxb.) is a perennial shrub from Marantaceace family. In traditional medicine, rhizome of the plant is used in fever and stem is used in earache. We aimed to substantiate these therapeutic claims by examining their effects in mice model. Antinociceptive effect was evaluated by three pain models and antipyretic effect was tested by yeast induced hyperthermia experiment. Influence of mice sexes on these pharmacological effects was examined by performing experiments separately on male and female mice. Quantitative analyses of total phenols and flavonoids were performed. Antinociceptive effects showed striking sex dimorphism. In hind paw licking test, male mice showed significant reductions in licking in both phases for both rhizome and stem extracts while significant effect was observed only in late phase in female mice. In writhing test, antinociception is more profound in male than in female. In hot plate test, stem was more effective than rhizome in male mice while female mice produced little effect for both extracts. Antipyretic experiment also showed varied effect in male and female mice; both extracts showed significant decrease in body temperatures. Rhizome showed greater effect in female mice while stem was more effective in male mice. Total phenol and flavonoid in rhizome were found 103.08 mg GAE (gallic acid equivalent) and 9.07mg QE (quercetin equivalent) respectively while in stem, these were 43.39mg GAE and 20.93 QE. Antinociceptive and antipyretic effects of rhizome and stem extracts endorsed the traditional uses of S. dichotomus. Also, differential effects based on mouse sex indicate the prerequisite of both male and female mice model in therapeutic evaluations of plant extract.